Diagnostic accuracy of leptospirosis whole-cell lateral flow assays: a systematic review and meta-analysis. (April 2019) - Maze, M.J.; Sharples, K.J.; Allan, K.J.; Rubach, M.P.; Crump, J.A.
Abstract: Background: Leptospirosis is under-diagnosed by clinicians in many high-incidence countries, because reference diagnostic tests are largely unavailable. Lateral flow assays (LFA) that use antigen derived from heat-treated whole cell Leptospira biflexa serovar Patoc have the potential to improve leptospirosis diagnosis in resource-limited settings. Objectives: We sought to summarize estimates of sensitivity and specificity of LFA by conducting a systematic review and meta-analysis of evaluations of the accuracy of LFA to diagnose human leptospirosis. Data sources: On 4 July 2017 we searched three medical databases. Study eligibility criteriaArticles were included if they were a study of LFA sensitivity and specificity. Participants: Patients with suspected leptospirosis. Interventions: Nil. Methods: For included articles, we assessed study quality, characteristics of participants and diagnostic testing methods. We estimated sensitivity and specificity for each study against the study-defined case definition as the reference standard, and performed a meta-analysis using a random-effects bivariate model. Results: Our search identified 225 unique reports, of which we included nine (4%) published reports containing 11 studies. We classified one (9%) study as high quality. Nine (82%) studies used reference tests with considerable risk of misclassification. Our pooled estimates of sensitivity and specificity were 79% (95% CI 70%–86%) and 92% (95% CI 85%–96%), respectively. Conclusions: As the evidence base for determining the accuracy of LFA is small and at risk of bias, pooled estimates of sensitivity and specificity should be interpreted with caution. Further studies should use either reference tests with high sensitivity and specificity or statistical techniques that account for an imperfect reference standard.